Room for Fear: Using Our Own Personal Stories in Teacher Education - Mary Jane Harkins; Michelle Forrest; Terrah Keener (University of Windsor, 2009)
In this paper, we explore how stories can serve as a pedagogical strategy in pre-service teacher education. Sharing concerns for students facing the complexities of today's classrooms evoked memories of moments from our own early years as teachers. Making sense of our fears many years later, led to the recognition that our students are facing similar situations. Through the exploration of our stories we demonstrate how we have gained insights into teaching and begun to make meaning from our experiences. Key to these stories is a sense of beliefs being disrupted by a fear of teaching.